Implementation of GPC and 2GPC on SISO water tank system - Para Sarath Babu. (2013)
The tuning for set point tracking and disturbance rejection in a control algorithm cannot be achieved without sacrificing performance. Model mismatch has also a significant impact on the controller design. In order to overcome the above difficulties a Parallel Control Structure is implemented using General Predictive Control algorithm, which overcomes problems of tuning the controller parameters independently and to achieve robustness in the controller. Parallel Control Structure with General Predictive Control algorithm is implemented on a Single Input Single Output (SISO) water tank system and the simulation studies also carried out. The results from the experiment shows that parallel control structure can be used to achieve independent tuning for set-point tracking and disturbance rejection with a tolerance of 20 percent of model mismatch. The simulation also gives prospective information about the independent tuning under normal conditions and during mismatch conditions.